Tourist guides’ perceptions of cultural heritage tourism in South Africa - Merwe Clinton David van der (Bulletin of Geography. Socio-Economic Series)
Heritage tourism is a fast growing niche of cultural tourism worldwide. In Africa, several countries, including South Africa, place great emphasis on the growth of heritage tourism because of its potential for local economic development. Cultural and heritage tourism are being advocated as an important niche within the South African economy. This paper explores the perceptions of cultural heritage tourist guides in South Africa towards heritage tourism, it is argued that the country’s National Department of Tourism must improve the poor governance and poor management of South African heritage assets, and enhance the preservation, transformation and segmented marketing of South Africa’s cultural assets (at all levels of government) in order to sustain and grow cultural tourism in the future.